Upaya Perpustakaan dalam Membangun Kolaborasi Riset Pustakawan di Universitas Sebelas Maret Surakarta - Siti Nurkamilah; Wahid Nashihuddin (Tik Ilmeu : Jurnal Ilmu Perpustakaan dan Informasi, 2021)
One of the ways to increase librarian's scientific publications is through research collaboration. Research collaboration is an intellectual activity that emphasizes the need for collaboration, communication, and the division of tasks of the research team in a research project. Librarians can carry out research collaborations with academics to enhance their role as research collaborators for institutions. The UNS Library has provided research information and research consulting services called "Klinik Pustaka Ilmiah”. This research aims to identify the various efforts of the UNS Library in increasing librarian research publications, and building research collaborations of librarians with academics (lecturers and students). This study uses a qualitative approach, with data sources from interviews and documentation. The results showed that the UNS Library's "Klinik Pustaka Ilmiah" service really supports the collaborative research activities of academic librarians, and the library has made various efforts to increase research publications and librarian research collaborations. Researchers also suggest that the UNS Library be more active to encourage librarians in institutional research collaborations, and librarians also need to improve their research competence on an ongoing basis.